Efeitos do dióxido de carbono e cianeto de potássio sobre os limiares das respostas de defesa induzidas pela estimulação elétrica da matéria cinzenta periaquedutal dorsal de ratos - Brunóro, Fagna Giacomin Schimitel (2009)
Panic attacks are precipitated by either the infusion of sodium lactate (0.5 M, I.V.) or the inalação inhalation of carbon dioxide (CO2 5%) by patients with panic disorder, but not healthy volunteers or patients with psychiatric disorders other than panic. Accordingly, it was suggested that panic attacks are the misfiring of a suffocation alarm system. On the other hand, the defensive behaviors produced by electrical stimulation of the dorsal half of the periaqueductal gray matter (DPAG) have been proposed as a model of panic attacks. Anedoctal observations also showed that intravenous injections of sublethal doses of potassium cyanide (KCN) produce behaviors akin to the defensive behaviors of the rat. Therefore, the present study examined first the behavioral effects of electrical stimulation of DPAG (0-60 µA), CO2 (0-13%) and KCN (10-80 µg, I.V.). DPAG-evoked defensive behaviors were then evaluated in the presence of 8% or 13%CO2 or during the infusion of a low dose of KCN (20 µg, 30 s, I.V.). CO2 and KCN effects were compared to controls in room air or infused with saline (I.V.). The day after the KCN and saline sessions, the DPAG was subjected to an electrolytic lesion and, 24 h after that, the rats were injected with a high but sublethal dose of KCN (80 µg). Intensity- and dose-response curves were evaluated by logistic threshold analysis and likelihood ratio χ 2 tests. KCN effects before and after lesions of DPAG were assessed by Pearson’s χ 2 . The exposure to CO2 produced only an state of hyporeactive immobility. In contrast, KCN produced all defesive responses of the rat. On the other hand, while the CO2 increased the thresholds of DPAG-evoked exophthalmus, immobility, trotting and galloping, KCN produced a significant reduction in the thresholds of trotting and galloping. DPAG lesions abolished KCN- 6 evoked responses of immobility, galloping and jumping and produced a marked attenuation of do trotting, exophthalmus and defecation. These results support the involvement of DPAG in a suffocation alarm system.